Ekonomi Islam dalam Mendukung Tujuan Pembangun Berkelanjutan SDGs - Aldi, Muhammad; Khairanis, Retisfa (PENG: Jurnal Ekonomi dan Manajemen, 2025)
The purpose of this study is to analyze the role of Islamic economics in supporting the achievement of the Sustainable Development Goals (SDGs). Islamic economics, with its principles of social justice, inclusiveness and sustainability, offers unique solutions to address global challenges such as poverty, inequality and environmental degradation. This research aims to identify the specific contributions of Islamic economic instruments, such as zakat, waqf, and Islamic financing, in achieving the SDGs targets. The research method used is a qualitative approach with literature analysis and case studies. Data were collected from various primary and secondary sources, including scientific journals, reports of international organizations, as well as best practices from countries implementing Islamic economics. The case study involved an analysis of the zakat program in Indonesia and the role of green sukuk in funding sustainable projects. The results show that Islamic economics significantly supports several key pillars of the SDGs. Zakat contributes to poverty alleviation (SDG 1) and inequality reduction (SDG 10), while waqf and green sukuk support sustainable infrastructure development (SDG 9) and climate action (SDG 13). In addition, Islamic economic values encourage responsible consumption and production patterns (SDG 12). The implications of this research show that the integration of Islamic economic instruments in development policies can accelerate the achievement of the SDGs. This research contributes to the development economics literature by offering an Islamic values-based perspective to face global challenges, while providing practical guidance for policy makers, Islamic financial institutions, and philanthropic organizations